Toán 9 Chuyên đề Rút gọn biểu thức

Darkness Evolution

Duke of Mathematics
Thành viên
27 Tháng năm 2020
620
1,101
146
15
Vĩnh Phúc
THCS Vĩnh Yên
Làm 4a với 6b thôi...
4a)
[tex]A=\sqrt{\frac{3\sqrt{3}-4}{2\sqrt{3}+1}}-\sqrt{\frac{\sqrt{3}+4}{5-2\sqrt{3}}}= \sqrt{\frac{(3\sqrt{3}-4)(2\sqrt{3}-1)}{(2\sqrt{3})^2-1}}-\sqrt{\frac{(5+2\sqrt{3})(\sqrt{3}+4)}{5^2-(2\sqrt{3})^2}}[/tex]
$= \sqrt{\frac{22-11\sqrt{3}}{11}}-\sqrt{\frac{26+13\sqrt{3}}{13}}$
$= \sqrt{2-\sqrt{3}}-\sqrt{2+\sqrt{3}}$
$=-\sqrt{2-\sqrt{3}+2+\sqrt{3}-2 \sqrt{(2-\sqrt{3})(2+\sqrt{3})}}$(Vì $A<0$)
$=-\sqrt{2}$
6b)
$B=\sqrt{5(4-2\sqrt{3})}+ \sqrt{5(7-4\sqrt{3})}$
$B=\sqrt{5(\sqrt{3}-1)^2}+\sqrt{5(2-\sqrt{3})^2}$
$B= (\sqrt{3}-1)\sqrt{5}+ (2-\sqrt{3})\sqrt{5}$
$B=(\sqrt{3}-1+2-\sqrt{3})\sqrt{5}=\sqrt{5}$
 
Top Bottom